Effect of different motor speeds of single cylinder compressor on refrigeration system / Mohammad Rizauddin Mohd Nasir - Mohd Nasir, Mohammad Rizauddin (2022)
The refrigerator has a compressor to make sure the refrigeration cycle is always working. Compressor is an important device in refrigeration system to compress working fluid thus giving pressure to flow. The problem is how the different motor speed in the compressor can completely give an effect to the refrigeration system. The objectives are to find the relation between the speeds of single cylinder of compressor and the changes of working fluid in refrigeration system. Then to evaluate the efficiency of compressor. In this study, various speeds of motor and the changes of temperature are considered. Water flow rate is constant at 3 Lpm that will be implemented during the development of this project by calculating the data that have recorded, make a relation, and make more than one graph to easily present the final work.